A parallel hybrid modular multilevel converter for high voltage DC applications - Amankwah, Emmanuel K. (2013)
Reliability and efficiency of power transmission has been at the forefront of research for some time and is currently being given critical consideration due to the increased dependence on electrical energy. With the increased demand for electricity, engineers are considering different methods of supply arrangement to improve the security of electricity supply. High Voltage Direct Current (HVDC) transmission is a technology that avails itself for distance power transmission, interconnection of asynchronous networks and cross sea or offshore power transmission. The main element of an HVDC system is the AC/DC or DC/AC power converter.